2021
DOI: 10.3389/fpls.2021.591587
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Field Phenotyping for Plant Height Using UAV-Based RGB Imagery in Wheat Breeding Lines: Feasibility and Validation

Abstract: Plant height (PH) is an essential trait in the screening of most crops. While in crops such as wheat, medium stature helps reduce lodging, tall plants are preferred to increase total above-ground biomass. PH is an easy trait to measure manually, although it can be labor-intense depending on the number of plots. There is an increasing demand for alternative approaches to estimate PH in a higher throughput mode. Crop surface models (CSMs) derived from dense point clouds generated via aerial imagery could be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 92 publications
(90 reference statements)
4
56
0
Order By: Relevance
“…These images were then computationally stitched together followed by the trait extraction using high-performance computers. In the studies by Crain et al ( 2018 ), Rutkoski et al ( 2016 ), and Volpato et al ( 2021 ), expensive phenotyping equipment [i.e., global positioning system (GPS) or multispectral scanners] was used to evaluate plants. To our knowledge, this is the first study that was conducted with low-cost tools and analysis that could be completed with a personal computer (i.e., resources available to many national breeding programs).…”
Section: Discussionmentioning
confidence: 99%
“…These images were then computationally stitched together followed by the trait extraction using high-performance computers. In the studies by Crain et al ( 2018 ), Rutkoski et al ( 2016 ), and Volpato et al ( 2021 ), expensive phenotyping equipment [i.e., global positioning system (GPS) or multispectral scanners] was used to evaluate plants. To our knowledge, this is the first study that was conducted with low-cost tools and analysis that could be completed with a personal computer (i.e., resources available to many national breeding programs).…”
Section: Discussionmentioning
confidence: 99%
“…ML may be particularly useful in unexplored isolated pockets of diversity, which contain allelic variants otherwise eroded from modern genotypes [192,193]. These predictive tools may additionally accommodate multi-trait [194] multi-environment [195,196] scores within the growing fields of enviromics [197][198][199], green house speed phenotyping [126,200], simulation-based breeding [99,124], hyperspectral imaging (HSI) [201][202][203], and epigenetics [204], allowing for better resolution and pace to detect and use standing adaptation.…”
Section: Geavs Geavsmentioning
confidence: 99%
“…In addition, illuminations, ambient light conditions, and external disturbances, such as wind and occlusion, can significantly affect the quality of the reconstructed point clouds. It has been concluded that the main challenge with the SfM technique, especially in large field experiments consisting of hundreds of plots, is the requirement for reference objects when accurate metric data are not available [36][37][38][39]. Research works involving other common approaches for determining crop size traits, such as descriptive and outline-based shape analysis methods [39], have incorporated mathematical models, such as Fourier [40,41] and wavelet analysis [42], as well as artificial intelligence techniques [43,44].…”
Section: Literature Review and Background Studymentioning
confidence: 99%